Integration of renewable energy and sustainable development with strategic planning in the mining industry - Mahdi Pouresmaieli; Mohammad Ataei; Ali Nouri Qarahasanlou; Abbas Barabadi (Results in Engineering, 2023)
With an increase in the world population, the global demand for minerals is rising, increasing energy consumption. Due to the distance of mines from urban areas, the energy required for mining is highly dependent on fossil fuels. Using renewable energies is an effective solution to reducing this problem. This study examines the challenges and opportunities of integrating renewable energy into mining operations and the impact of this integration on the attainment of Sustainable Development Goals (SDG). The present study also investigates the strategic management of renewable energy use in the mining sector via the Strengths, Weaknesses, Opportunities, and Threats (SWOT) method. The results indicate that despite the high potentialities of renewable energy in mining, much more investigation is required for the technical use of this technology in the mining industry. Using renewable energy can create new jobs, reduce environmental pollution, increase knowledge in the mining area, create a circular economy in the mining industry, and reduce mining operating costs. All mentioned factors can have a positive effect on sustainable development indicators. On the other hand, mine owners' lack of information about the positive effects of renewable energy, high investment, lack of skilled labor, and high maintenance costs can create challenges for using renewable energy in mines. The SWOT strategic management analysis results demonstrate that the strengths and possible opportunities of using this technology in mining outweigh the weaknesses and possible threats. Hence, the aggressive strategy, defined as the maximum use of strengths to benefit from created opportunities optimally, is suggested.